1529 Management of A Rare Case of Bilateral Persistent Sciatic Artery Aneurysms Causing Critical Limb Ischaemia With Staged Embolisation And Femoropopliteal Bypass: A Case Report. (12th October 2021) - Lau, S; MacLeod, C; Vesey, A; Lau, P F; Ghibu, P
Abstract: Introduction: Bilateral persistent sciatic arteries (PSA) are rare with an incidence of 0.001%. They represent a persistence of the embryonic axial limb circulation via the internal iliac artery. Normally the PSA involutes and is replaced by the superficial femoral artery (SFA). Failure of regression leads to a PSA with varying configurations. Up to 50% of PSAs are aneurysmal and may present with rupture or acute/chronic ischaemia, typically at 40-50 years old. Case Report: A 74-year-old female presented with limb threatening ischaemia manifesting with rest pain, sensory deficit and early tissue loss (Rutherford IIb). She had a left femoral pulse but absent pulses distally. Pedal pulses were noted on the contralateral limb. CT angiogram revealed bilateral complete PSAs with incomplete hypoplastic SFAs (Pillet-Gauffre 2a). Both PSAs were aneurysmal; the left PSA was acutely occluded distal to the aneurysm. She underwent staged intervention with percutaneous embolisation of the left PSA, followed by femoropopliteal bypass. She was discharged six days later with good symptomatic relief at one month follow up. We are planning to treat the contralateral limb in a similar manner electively in case complications occur. Conclusions: PSAs are commonly associated with limb threatening complications but due to their rarity there are limited reports on the management of this condition. Here we can report a good outcome in a late presentation using staged embolisation with open reconstruction.